Safe Medication Management for Polymedicated Home-Dwelling Older Adults after Hospital Discharge: A Qualitative Study of Older Adults, Informal Caregivers and Healthcare Professionals' Perspectives - Filipa Pereira; Marion Bieri; Maria Manuela Martins; María del Río Carral; Henk Verloo (MDPI AG, 2022)
Safe medication management is particularly challenging among polymedicated home-dwelling older adults after hospital discharge. This study aimed to identify and categorise the stressors experienced and reconstitution strategies adopted by older adults, their informal caregivers, and healthcare professionals as they manage older adults' medications after hospital discharge. A primary study collected the perspectives of 28 older adults, 17 informal caregivers, and 13 healthcare professionals using a qualitative descriptive design. The Neuman Systems Model was used as the basis for a secondary deductive content analysis. Findings revealed that post-discharge medication management at home involved numerous stressors, often including dysfunctions in communication, collaboration, and coordination between the multiple stakeholders involved. Reconstitution strategies for safe medication management were not always successful or satisfactory and were sometimes identified as stressors themselves. Older adults, informal caregivers, and healthcare professionals' perspectives highlighted several potential opportunities for improving safe medication management through nurse-led, interprofessional, patient-centred practices.